If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(z+4)/(z+7)+(z/4)=(2z+11)/(z+7)
We move all terms to the left:
(z+4)/(z+7)+(z/4)-((2z+11)/(z+7))=0
Domain of the equation: (z+7)!=0
We move all terms containing z to the left, all other terms to the right
z!=-7
z∈R
Domain of the equation: (z+7))!=0We add all the numbers together, and all the variables
z∈R
(z+4)/(z+7)+(+z/4)-((2z+11)/(z+7))=0
We get rid of parentheses
(z+4)/(z+7)+z/4-((2z+11)/(z+7))=0
We calculate fractions
((z+4)*4*(z+7)))/((z+7)*4*(z+7)))+(z*(z+7)*(z+7)))/((z+7)*4*(z+7)))+(-((2z+11)*(z+7)*4)/((z+7)*4*(z+7)))=0
We can not solve this equation
| -3+1+2x=-2x-5 | | 94x=11*3*x | | (12x-8)+40=180 | | 2(x+2)^2-128=0 | | m4+4=7 | | x/9-6=17/18 | | m4+ 4= 7 | | 30=2a+50 | | 2(x+2)^2-57=71 | | 0.4x+0.9x=0.8x-0.3 | | 4(2×5)=g | | r2+7=10 | | -4=1/3z+2 | | r2+ 7= 10 | | x^2+10x+9=16 | | -2g+-4=-8 | | (x-1)(x-4)(2x+3)=0 | | -x+√4x+36=1 | | 5/2x+5=20 | | 7x+3=174 | | 25x^2-61x+36=0 | | 6^x=20x | | -8(6-4m)=176 | | (0.3/0.08)=x | | 2/3x^2-1/2x-3/4=0 | | 0=10.5-0.4x^2 | | 3/2-6x=24 | | -10(9k-9)=-10(9+7k) | | 1/2d=-5 | | 3(n-5)=7-2(n+1) | | 8(x+2)+1=2x+6(3+x) | | 251=33-v |